Promotion and Marketing Role in Increasing The Amount of Umrah Package Sales at PT Turisina Buana Tour and Travel - Quamila, Dyandra Shafa (Journal of Indonesian Tourism and Policy Studies, 2025)
This study examines the role of promotion and marketing in increasing the sales of Umrah packages at PT Turisina Buana Tour and Travel. The aim of this research is to explore how promotional activities and marketing strategies implemented through social media can enhance the number of Umrah pilgrims, as well as to identify the supporting and inhibiting factors affecting their effectiveness. A qualitative approach was employed, with data collected through observation and in-depth interviews involving the Director of PT Turisina Buana and a customer who has used the company’s services. The findings indicate that social media promotion, supported by the application of marketing mix strategies and effective promotional elements, significantly contributes to improving the company's image and increasing the number of Umrah pilgrims. Nonetheless, several factors were identified that influence implementation, including supporting factors such as ease of information access and inhibiting factors such as limited human resources for managing social media. These insights may serve as a basis for evaluating and enhancing the company's promotional strategies in the future.